2015
DOI: 10.2169/internalmedicine.54.3337
|View full text |Cite
|
Sign up to set email alerts
|

Successful Conservative Treatment of Emphysematous Gastritis

Abstract: Emphysematous gastritis is an extremely rare disease with an unfavorable prognosis. To date, very few studies have been conducted regarding the intragastric recovery process based on endoscopic findings. We herein report a case of emphysematous gastritis that improved with long-term (five months) conservative treatment in which we were able to observe the intragastric recovery process endoscopically. In cases in which emphysematous gastritis is suspected, it is important to provide prompt diagnostic imaging (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 12 publications
2
25
0
1
Order By: Relevance
“…There have been cases of associated bacterial infection with Clostridium welchii, Escherichia coli, Streptococcus, Bacillus subtilis, proteus, Pseudomonas and Enterobacter [1,4]. Our patient was There is no established diagnostic criteria for EG [2]. Previous studies have suggested severe symptoms, characteristic medical imaging and bacterial infection as diagnostic markers.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…There have been cases of associated bacterial infection with Clostridium welchii, Escherichia coli, Streptococcus, Bacillus subtilis, proteus, Pseudomonas and Enterobacter [1,4]. Our patient was There is no established diagnostic criteria for EG [2]. Previous studies have suggested severe symptoms, characteristic medical imaging and bacterial infection as diagnostic markers.…”
Section: Discussionmentioning
confidence: 75%
“…Known associated conditions include ingestion of corrosives, alcohol abuse, renal failure, diabetes, non-steroidal anti-inflammatory drug usage, pancreatitis, gastroenteritis and recent abdominal surgery [2,3]. There have been cases of associated bacterial infection with Clostridium welchii, Escherichia coli, Streptococcus, Bacillus subtilis, proteus, Pseudomonas and Enterobacter [1,4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emphysematous gastritis (EG) is a rare phenomenon that is defined by gas within the gastric wall (Takano et al 2015). EG is often a fatal condition caused by gas-producing bacteria with mortality rates as high as 55-61% (Takano et al 2015, Chen 2016, Watson et al 2016.…”
Section: Introductionmentioning
confidence: 99%